(3QSGdI aj Gdbhd aj GdfaS (B( (3GdeNJUQ ef cJGH CQSWh hSGFQ GdadGSaI (B)s - (3CHh YeQ GdcfOj , CHh jYbhH Hf eMeO Hf ESMGb GdcfOj, GdcfOj,J (B355 (3g` s
(3ChdgG (B:s
(3QSGdI CHj jYbhH Hf eMeO Hf ESMb GdcfOi ai Gdbhd ai GdfaS GdeNJUQ ef cJGH GQSWh hSGFQ GdadGSaI aCbhd Ef GdfaS HSjWI PGJ TQa hceGd YXjeI GdTCf hLhgQgG ef LhgQ GdHGQi YR hLd s
(3BNQgG (B:s
(3Ke jUjQ Edi GdYGde GdMbjbi ajHbi ajg CHO GdGHOjf hGNJUQfGg ef bhdge Ef GdfaS LhgQ HSjW ajage eG cSH Hg Edjc hGdMeO ddg QH GdYGdejf hGdUdGI Ydi eMeO hGdg GLeYjf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B148 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B142s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs